THE ROLE OF SPORTIVE ACTIVITIES IN CHILDREN'S PERSONALITY DEVELOPMENT - Cristian SANTA; Onela SANTA; Alin BACIU; Paul SZABO-ALEXI (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2015)
The athlete is the main subject of performance generator and is being defined by a large number of attributes, some of which are characteristic for achieving it. He can develop only if certain conditions are met both in terms of correlating interdependent attributes, qualities – skills and the environmental factors, social, material, teaching. The relationships between members of a community are subject to numerous factors such as: psychological peculiarities of the athletes, the general orientation, the reasons of the proposed activity, attitudes "built" in life and the society in which they live. There are a few things to note: first, the game strengthens a child physically, it embodies the taste of performance and the means to achieve it. Secondly, the game creates teamwork skills to synchronize their actions with those of others to achieve a common goal. A third, the game causes a good mood, cheerful, giving the people the ability to clear their heads and have fun giving more lust for life.